Age Constraints Effectiveness on the Human Community Based Genetic Algorithm (HCBGA) - Nagham A. Al-Madi; Amnah A. El-Obaid (Institute of Advanced Engineering and Science, 2018)
In this paper, we use under-age constraints and apply it to the Traveling Salesman Problem (TSP). Values and results concerning the averages and best fits of both, the Simple Standard Genetic Algorithm (SGA), and an improved approach of Genetic Algorithms named Human Community Based Genetic Algorithm (HCBGA) are being compared. Results from the TSP test on Human Community Based Genetic Algorithm (HCBGA) are presented. Best fit solutions towards slowing the convergence of solutions in different populations of different generations show better results in the Human Community Based Genetic Algorithm (HCBGA) than the Simple Standard Genetic Algorithm (SGA).